Treblinka : archaeological investigations and artistic responses - Sturdy Colls, Caroline 1985- (Centre of Archaeology book series: Special issue, 2016)
Between 800,000 and 1 million people lost their lives at Treblinka extermination camp during the Holocaust. A further 10,000 perished in the nearby labour camp as a result of the Nazi death through work policy and ad hoc executions. Since 2007, both camps have been the subject of forensic archaeological research in order to reveal new insights into the nature and extent of Nazi persecution. This book presents the major findings of the archaeological work, which included the discovery of the gas chambers, personal effects of the victims and mass graves. It also includes artistic responses to these findings, which were commissioned as part of the international exhibition “Finding Treblinka”